F. Nietzsche: Metaphorical Architecture of Classical Thought and Its Symptomatics - Mickevičius, Arūnas (Problemos, 2004)
The article deals with F. Nietzsche’s attitude to classical thought. Nietzsche’s theoretical construct are based on the principle Wille zur Macht, where he emphatically praised active forces, and accused all classical thinking of turning away from life and associated it with reactive, negative forces. This construct is characterised by independly manifested speculative forms: genealogising, typology and symptomatic. Nietzsche’s philosophy, based on will to power, denies the exceptionally unique true opinion of the world and offers insteed a variety of interpretations; foresees the possibility to look at world through different eyes, i. e determines a perspectivist approach to the world. Nietzsche stated that conceptual language, metaphoricin essence, cannot, through its anthropomorphic activity transmit “true”, “objective” information about world and has no right to refer to the only truth, accsesible to only. According to Nietzsche conceptual language of classical though is metaphorical. In describing architectural metaphors of classical thinking he show that it is reactive, life denying, that the assumed grandeur of it in fact hides simplificity and poverty of life. On the other hand Nietzsche attempts to release metaphoric power from the single axiom of Truth, to release creativity, to legitimize perspective, interpretive view of the world, based on the mentioned “will to power” principle, and related to assertive powers of active life.